Conserved and variable natural killer cell receptors: diverse approaches to viral infections - Bastidas‐Legarda, Leidy Y. (Immunology, 2019)
Natural killer (NK) cells are lymphocytes of the innate immune system with essential roles during viral infections. NK cell functions are mediated through a repertoire of non‐rearranging inhibitory and activating receptors that interact with major histocompatibility complex (MHC)–peptide complexes on the surface of infected cells. Recent work studying the conserved CD94–NKG2A and variable killer cell immunoglobulin‐like receptor–MHC systems suggest that these two receptor families may have subtly different properties in terms of interactions with MHC class I bound peptides, and in recognition of down‐regulation of MHC class I. In this review, we discuss how these properties generate diversity in the NK cell response to viruses.